Sodium Monoiodoacetate Dose-Dependent Changes in Matrix Metalloproteinases and Inflammatory Components as Prognostic Factors for the Progression of Osteoarthritis - Bryk, Marta; Chwastek, Jakub; Mlost, Jakub; Kostrzewa, Magdalena; Starowicz, Katarzyna (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is a degenerative joint disease that primarily affects people over 65 years old. During OA progression irreversible cartilage, synovial membrane and subchondral bone degradation is observed, which results in the development of difficult-to-treat chronic pain. One of the most important factors in OA progression is joint inflammation. Both proinflammatory and anti-inflammatory factors, as well as extracellular matrix degradation enzymes (matrix metalloproteinases (MMPs), play an important role in disease development. One of the most widely used animal OA models involves an intra-articular injection of sodium monoiodoacetate (MIA) directly into the joint capsule, which results in glycolysis inhibition in chondrocytes and cartilage degeneration. This model mimics the degenerative changes observed in OA patients. However, the dose of MIA varies in the literature, ranging from 0.5 mg to 4.8 mg. The aim of our study was to characterize grading changes after injection of 1, 2 or 3 mg of MIA at the behavioral and molecular levels over a 28-day period. In the behavioral studies, MIA injection at all doses resulted in a gradual increase in tactile allodynia and resulted in abnormal weight bearing during free walking sequences. At several days post-OA induction, cartilage, synovial membrane and synovial fluid samples were collected, and qPCR and Western blot analyses were performed. We observed significant dose- and time-dependent changes in both gene expression and protein secretion levels. Inflammatory factors (CCL2, CXCL1, IL-1β, COMP) increased at the beginning of the experiment, indicating a transient inflammatory state connected to the MIA injection and, in more severe OA, also in the advanced stages of the disease. Overall, the results in the 1 mg MIA group were not consistently clear, indicating that the lowest tested dose may not be sufficient to induce long-lasting OA-like changes at the molecular level. In the 2 mg MIA group, significant alterations in the measured factors were observed. In the 3 mg MIA group, MMP-2, MMP-3, MMP-9, and MMP-13 levels showed very strong upregulation, which may cause overly strong reactions in animals. Therefore, a dose of 2 mg appears optimal, as it induces significant but not excessive OA-like changes in a rat model.